Multi-objective based dynamic vehicle route guidance system - Lee, Chung Siong (2008)
Different kinds of traffic data in transportation network are presented and discussed. Historical data of Singapore road network are analyzed with regard to certain classification scheme. Using these sources of information Dijkstra’s and A*algorithm for reliable traffic forecasts is discussed.